Effects of eco-friendly cooling strategy on machining performance in micro-scale diamond turning of Ti–6Al–4V. (10th January 2020) - Huang, Peng; Li, Hongcheng; Zhu, Wu-Le; Wang, Haitao; Zhang, Guoqing; Wu, Xiaoyu; To, Suet; Zhu, Zhiwei
Abstract: Titanium alloys are difficult-to-cut materials due to their low elastic modulus and poor thermal conductivity. To deepen the understanding of the cutting performance for Ti–6Al–4V under various eco-friendly cooling conditions, surface integrity, cutting forces, and tool wear were comprehensively investigated through cutting experiments implementing three cooling methods, namely, cryogenic gas (CG), minimum quantity lubrication (MQL), and a combination of CG and MQL (CG + MQL), respectively. The results show that the lowest surface roughness ( S a  = 76.71 nm) was achieved at a low spindle speed under the CG + MQL cooling conditions. This suggests that of the three cooling methods, the CG + MQL hybrid cooling method achieved the highest cooling efficiency. Compared with the MQL cooling method, the CG + MQL cooling method led to more pronounced tool wear and material adhesion due to reduced oil-based lubricity caused by low temperatures. Under the MQL cooling conditions, the elastic recovery of Ti–6Al–4V accelerated the formation of micro-cleavages on the clearance face of the diamond tool. Additionally, the depth of cut was also comparable to the tool edge radius in the micro-scale diamond turning. Compared with the conventional turning of Ti–6Al–4V, this round-edge effect, combined with the adhesion and built-up edge, led to a relatively stronger friction effect, evidenced by an increase in the coefficient of friction from 1.027 to 3.532, and higher specific cutting energy under all the cooling conditions in micro-scale diamond turning.